Urogenital Traumas: An Emergency Department Experience - Gözde Yılmaz Dursun; Rukiye Aytekin Akdağ; Haticenur Karakartal; Necmi Baykan; Ömer Salt (OSMANGAZİ JOURNAL OF MEDICINE, 2026)
The aim of this study is to retrospectively evaluate the demographic characteristics, types of trauma, clinical outcomes, and treatment approaches of urogenital trauma cases presenting to the emergency department. In this retrospective study, the medical records of a total of 80 patients who presented to the emergency department with trauma between January 1, 2024, and December 31, 2024, were examined. Information on the patients' age, gender, time of presentation, type of trauma, treatment method, and emergency outcome was analyzed. Descriptive statistics were used; chi-square test and one-way ANOVA were applied for intergroup comparisons. A total of 80 urogenital trauma patients who presented to the emergency department during the study period were evaluated. Of the patients, 81.3% were male. Examination of trauma types revealed that 67.5% (n:54) had multitrauma, whereas 32.5% (n:26) had isolated urogenital trauma. Regarding clinical outcomes, 28.8% of the patients were discharged (n:23), 70% were hospitalized (n:56), and 1.3% died in the emergency department (n:1). The overall mean age of the cohort was 40.27 ± 18.03 years. While 90.7% of multitrauma patients (n:49) required hospitalization, 73.1% of isolated urogenital trauma cases (n:19) were discharged (p<0.001). Age, trauma type, and treatment strategy are key determinants in the clinical management of urogenital trauma. Cases associated with multitrauma carry a higher risk of hospitalization and adverse outcomes. This study contributes valuable insight into the emergency department evaluation and management of urogenital injuries. A total of 7 patients required surgical intervention, and all of them underwent inpatient management.